2007
DOI: 10.1111/j.1365-2265.2007.02908.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiling and in vitro studies of murine bone growth using biological fluids from children with juvenile idiopathic arthritis

Abstract: SF and serum JIA samples can impair bone growth at the growth plate. In synovial fluid, the effect is variable but resistant to treatment with IL-1beta, IL-6 and TNF-alpha specific antibodies and IGF-1, suggesting that other factors in this biological fluid may also have an effect on longitudinal growth through IGF-1-independent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…It is unclear whether the sole growth-promoting effect of these drugs is through steroid sparing or direct effects on cytokines at the level of the growth plate. MacRae and colleagues recently showed that the inhibitory effect of serum and synovial fluid collected from children with JIA and containing a wide range of cytokines was not ameliorated by a combination of anti-IL-1β, TNFα and IL-6 antibodies, even at high concentrations [19]. In the rodent metatarsal model, which does not respond to GH stimulation, IGF-I administration ameliorates cytokine-induced growth retardation and reduces the level of chondrocyte apoptosis [21].…”
Section: Addressing the Cytokine Insult As A Means Of Promoting Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether the sole growth-promoting effect of these drugs is through steroid sparing or direct effects on cytokines at the level of the growth plate. MacRae and colleagues recently showed that the inhibitory effect of serum and synovial fluid collected from children with JIA and containing a wide range of cytokines was not ameliorated by a combination of anti-IL-1β, TNFα and IL-6 antibodies, even at high concentrations [19]. In the rodent metatarsal model, which does not respond to GH stimulation, IGF-I administration ameliorates cytokine-induced growth retardation and reduces the level of chondrocyte apoptosis [21].…”
Section: Addressing the Cytokine Insult As A Means Of Promoting Growthmentioning
confidence: 99%
“…Our knowledge about cytokine effects on human growth plate cartilage is limited. Most in vitro studies have concentrated on IL-6, IL-1β and TNFα; however, it is becoming increasingly clear that chronic inflammatory disease is associated with a variable level of alteration in many pro- and anti-inflammatory cytokines [19,20]. Both IL-1β and TNFα inhibit growth plate chondrocyte differentiation, increase apoptosis and inhibit cartilage-specific proteoglycan synthesis in ATDC5 murine growth plate cells as well as the rodent metatarsal model (fig.…”
Section: Cytokine Effects On Growthmentioning
confidence: 99%
“…Recent studies of in vitro longitudinal growth and growth plate chondrogenesis have led to a better understanding of the direct inhibitory effects of individual cytokines, as well as biological fluid from children with inflammation, on growth plate chondrogenesis [8,9,10]. Proinflammatory cytokines may also directly affect sex-steroid synthesis at the level of the gonads or through inhibiting gonadotrophin secretion and, thus, affect entry into and progress through puberty [11, 12].…”
Section: Inflammatory Cytokines In Ibdmentioning
confidence: 99%
“…Interleukin-1-β (IL-1β), tumour necrosis factor-α (TNF-α) and IL-6 remain the main proinflammatory cytokines that are studied in children with IBD [13, 14]. However, the inflammatory cytokine cascade is a complex balance between a number of pro- and anti-inflammatory cytokines, and the respective levels of these cytokines may vary between children with the same group of conditions [10, 15, 16]. This variability in the inflammatory milieu may explain some of the differences that are observed in the end-organ effects in patients, as well as the differences between in vitro studies and those in patients.…”
Section: Inflammatory Cytokines In Ibdmentioning
confidence: 99%
“…The major upregulated proinflammatory cytokines found in tissues or biological fluids from inflammatory bowel disease [5] or JIA [6,7,8] patients are interleukin (IL)-6, IL-1β and tumor necrosis factor (TNF)-α. They affect longitudinal bone growth by disrupting the growth hormone (GH)/insulin-like growth factor (IGF)-I axis [9,10].…”
Section: Introductionmentioning
confidence: 99%